Characterization of arsenic (III and V) adsorption on natural schwertmannite formed in acid coal mine drainage: Batch studies and spectroscopic observations. Issue 1 (February 2023) - Lee, Seon Yong; Kim, YoungJae; Kang, Sue A; Chang, Bongsu; Hur, Hyuck; Lee, Young Jae
Abstract: The adsorption behavior of As(III) and As(V) on natural schwertmannite (NSCH) was investigated using batch experiments and spectroscopic observations. NSCH showed comparable As adsorption capacities to synthetic schwertmannite (SSCH); particularly, a much higher affinity toward As(III) than toward As(V) was observed at pH 7, suggesting that NSCH is a promising As(III) adsorbent. As(III) adsorption increased with increasing pH and decreasing ionic strength (IS); effects of pH and IS on As(V) adsorption were opposite and negligible, respectively. These results indicated that the adsorption behaviors of As(III) and As(V) are significantly affected by the solution pH, IS, and As species. Speciation modeling and X-ray spectroscopic analyses revealed limited adsorption of As(V) on NSCH through the formation of only the bidentate binuclear corner-sharing inner-sphere complex, which was suppressed at a pH above the pHPZC because of the electrostatic repulsion between the anionic As(V) and the negatively charged NSCH surface. Compared to As(V), a greater amount of As(III) was adsorbed on NSCH, forming both bidentate mononuclear edge-sharing and bidentate binuclear corner-sharing inner-sphere complexes, including minor outer-sphere complexes. Some of the adsorbed As(III) was oxidized to As(V) during adsorption. Owing to the strong surface complexation, less than 4% of As(III) and As(V) were desorbed, indicating that stable As fixation is possible. These findings provided valuable information for the recycling of acid mine drainage sludge and its use in eco-friendly and cost-effective As attenuation. Graphical Abstract: ga1 Highlights: Mine drainage sludge was recycled for eco-friendly and cost-effective As attenuation. NSCH shows As(III) adsorption capacity (66.5 mg/g) comparable to that of SSCH. As(III) and As(V) show different adsorption behaviors with pH and ionic strength. Anion exchange with sulfate and surface complexation were responsible for As uptake. XPS and XAS revealed the inner-sphere configurations and partial oxidation of As(III).